Stigma and Discrimination Against People Living with HIV and AIDS in Nepal — A Review - Dhital, Krishna Prasad; Dhungana, Anjana; Rai, Hemanta Kala; Aryal, Sanskriti; Magar, Bishnu (NPRC Journal of Multidisciplinary Research, 2025)
Background: Stigma and discrimination against people living with HIV (PLHIV) in Nepal persist as major obstacles to effective prevention, testing, and treatment, despite improvements in public awareness. This stigma is deeply embedded in socio-cultural norms, moral judgments, and gender inequalities, which sustain discriminatory practices and social exclusion. Objective: This review aims to synthesize existing literature to understand the patterns, determinants, and impacts of HIV-related stigma in Nepal. It seeks to analyze the phenomenon through theoretical lenses and identify effective coping mechanisms and interventions. Methods: A narrative literature review was conducted. Peer-reviewed articles, national reports, and conceptual papers published up to October 2025 were identified from databases including PubMed, NepJOL, and Google Scholar using keywords related to HIV stigma, discrimination, gender, and Nepal. Data were extracted and synthesized thematically. Findings: The review confirms moderate to high levels of enacted and perceived stigma among PLHIV in Nepal, manifesting as social avoidance, gossip, and discrimination in healthcare and employment. Key determinants include persistent misconceptions about transmission, socio-cultural and religious values that moralize HIV, and entrenched gender inequality. Theoretical insights from structural-functionalism and feminism reveal how stigma functions to label PLHIV as "deviant" and disproportionately blame women. The consequences are severe, leading to poor ART adherence, delayed testing, and psychological distress. Interventions such as peer support are beneficial but are often hampered by a lack of integration with government systems and a failure to address underlying structural causes. Conclusion: HIV-related stigma in Nepal is a structural and cultural phenomenon, not merely an individual one. Awareness campaigns alone are insufficient to eliminate it. Effective stigma reduction requires multi-level interventions that target the deep-rooted socio-cultural and patriarchal norms that perpetuate discrimination. Implementation: To combat stigma effectively, policymakers and program implementers must move beyond awareness-raising to design structural interventions. This includes integrating sustainable, gender-sensitive stigma-reduction programs into national health strategies, strengthening anti-discrimination laws, and training healthcare workers to ensure confidentiality and non-discriminatory care.